Use of Technology to Prevent Illegal Fishing: A Case Study Perspective in the Natuna Sea - Geby Gita; Wan Jesica Febrianty (Austronesia Akademika, 2024)
The use of technology in preventing illegal fishing (IUU) is critical in addressing the ongoing challenges in Indonesia's Natuna Sea, a region vulnerable to violations like illegal fishing, unauthorized vessels, and unlicensed resource exploration. The primary objective of this research is to explore the role of technology in enhancing the monitoring and enforcement of fishing regulations. Various technological tools, such as Vessel Monitoring Systems (VMS), Humanless Underwater Sensor Technology (HUST), remote sensing, and Automatic Identification Systems (AIS), are employed to improve surveillance capabilities. These technologies help track fishing vessels, detect suspicious activities, and gather evidence for legal enforcement. A qualitative descriptive research approach is used to analyze the effectiveness of these technologies and their integration into Indonesia's fisheries management system. Data is collected from secondary sources, including legal documents and research studies. The results show that VMS, AIS, and remote sensing have significantly improved the monitoring of fishing activities in the Natuna Sea. However, challenges such as limited data coverage, vulnerability to manipulation, and inter-agency coordination remain. The study concludes that while technology has proven effective in combating illegal fishing, further efforts are needed to enhance its implementation, including strengthening legal frameworks, political support, and inter-agency collaboration to ensure sustainable fisheries management in the region.